Perception of the students of English Teaching, Atlantic Campus-University of Costa Rica at the beginning of the COVID-19 pandemic - Ramírez Zúñiga, Andrea (2022)
This article presents the results of a perception study carried out with 74 students of the English Teaching Career in the Atlantic Campus of University of Costa Rica during the first academic year 2020, to identify how the students perceived the virtualization of teaching caused by the pandemic. This research allowed us to determine that the teaching modality implemented was emergency remote education, which was intended not to expose students and teachers to face-to-face teaching. The methodology is based on a quantitative approach of descriptive scope that studies and interprets the students' perceptions based on the information obtained in an electronic questionnaire. The results indicate that students know about technology applied to teaching, which allows them to participate in educational activities in a virtual context, a situation that encourages individual work and a better organization of tasks, thanks to their ability to adapt and a responsible attitude towards study. Some educational activities perceived as useful were the exchange of documents, audiovisual material, online practices, and oral presentations. There were external factors that could limit the students' academic performance, such as Internet access and their physical and mental condition reflected in the stress and fatigue caused by studying daily behind a screen, with long classes and extensive work. Therefore, the I-2020 teaching process was perceived with positive and negative aspects on the part of the students, who had to face it to meet the proposed learning objectives.